Ta có:
B = \(\frac{2a+9}{a+3}-\frac{5a+17}{a+3}-\frac{3a}{a+3}\)
B = \(\frac{\left(2a+9\right)-\left(5a+17\right)-3a}{a+3}\)
B = \(\frac{2a+9-5a-17-3a}{a+3}\)
B = \(\frac{-6a-8}{a+3}=\frac{-6\left(a+3\right)+10}{a+3}=-6+\frac{10}{a+3}\)
Để B \(\in\)Z <=> 10 \(⋮\)a + 3 <=> a + 3 \(\in\)Ư(10) = {1; -1; 2; -2; 5; -5; 10; -10}
Lập bảng :
a + 3 | 1 | -1 | 2 | -2 | 5 | -5 | 10 | -10 |
a | -2 | -4 | -1 | -5 | 2 | -8 | 7 | -13 |
Vậy ...
\(B=\frac{2a+9}{a+3}-\frac{5a+17}{a+3}-\frac{3a}{a+3}\)
\(B=\frac{2a+9-5a-17-3a}{a+3}\)
\(B=\frac{-6a-8}{a+3}\inℤ\)
\(\Leftrightarrow-6a-8⋮a+3\)
\(\Rightarrow-6a-18+10⋮a+3\)
\(\Rightarrow-6\left(a+3\right)+10⋮a+3\)
\(\Rightarrow10⋮a+3\)
\(\Rightarrow a+3\in\left\{-1;1;-2;2;-5;5;-10;10\right\}\)
\(\Rightarrow a\in\left\{-4;-2;-5;-1;-8;2;-13;7\right\}\)